find the value of k if: xy²k= (4xy+3y)²-(4xy-3y)²
Answers
Answered by
6
Answer:
k = 48
Step-by-step explanation:
Given,
xy²k = (4xy + 3y)² - (4xy - 3y)²
Applying the formula: (a + b)² = a² + b² + 2ab
xy²k = [(4xy)² + (3y)² + (2 × 4xy × 3y)] - (4xy - 3y)²
Applying the formula: (a - b)² = a² + b² - 2ab
xy²k = [(4xy)² + (3y)² + (2 × 4xy × 3y)] - [(4xy)² + (3y)² - (2 × 4xy × 3y)]
xy²k = [(16x²y² + 9y² + 24xy²)] - [(16x²y² + 9y² - 24xy²)]
xy²k = 16x²y² + 9y² + 24xy² - 16x²y² - 9y² + 24xy²
xy²k = 48xy²
k = \frac{48xy^{2} }{xy^{2} }
∴ k = 48
Similar questions